2012
DOI: 10.1063/1.3679423
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic micro-structural uniformity of die-upset Nd-Fe-B magnets

Abstract: Die Fe 75.70 Co 4.45 B 5.76 Ga 0.47 magnets have been prepared with height reduction (h) in the range of 60 to 88%. The energy product as high as 50.4 MGOe was obtained in the sample with h $ 70%. The magnetic domains of the samples are revealed by using magnetic force microscopy (MFM). The average domain widths of the die-upset samples with surface normal parallel (//) and perpendicular (\) to the loading direction are in the range of w // : 0.4-0.6 lm; w \ : 0.9-3.8 lm, respectively. These interaction domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The coercivity increase with Hf content is largely a consequence of the reduced magnetization, because H c = 2K/M s [11], with some concentration dependence of . But for the complicated irregular interaction domains, the magnetic correlation length L (the average domain width) can be estimated by several methods [13][14][15][16][17][18]. The magnetocrystalline anisotropy parameter K and the spontaneous magnetization M 0 can be determined by fitting the hysteresis loops using the law of approach to saturation method [12].…”
Section: Resultsmentioning
confidence: 99%
“…The coercivity increase with Hf content is largely a consequence of the reduced magnetization, because H c = 2K/M s [11], with some concentration dependence of . But for the complicated irregular interaction domains, the magnetic correlation length L (the average domain width) can be estimated by several methods [13][14][15][16][17][18]. The magnetocrystalline anisotropy parameter K and the spontaneous magnetization M 0 can be determined by fitting the hysteresis loops using the law of approach to saturation method [12].…”
Section: Resultsmentioning
confidence: 99%
“…It is easy to define the average domain size for simple domain configurations by visual methods. But for the complicated irregular interaction domains the magnetic correlation length (the average domain width) can be estimated by several methods [13][14][15][16][17]. We have used the grain-size-analysis software incorporated in our MFM system to calculate from the MFM images as an average over the lateral dimension of the domains sizes.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of the die-upset Nd-Fe-B have shown that the magnetic domains at room temperature, referred to as interaction domains, are much larger than the grain size [15][16][17], because the grains are coupled due to intergranular exchange. The grains included in the interaction domain are almost in single-domain because their size (50-400 nm) is comparable to the single domain grain size for Nd 2 Fe 14 B [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore desirable to directly observe domain structures at elevated temperatures, rather than making indirect conclusions, for example from hysteresis loops. Magnetic force microscopy (MFM), a surface technique, has been widely used to reveal the magnetic domains of bulk permanent materials [17,[19][20][21][22][23][24]. Surprisingly, it has not been possible so far to record in-situ MFM images of die-upset Nd-Fe-B magnet above room temperature.…”
mentioning
confidence: 99%